A review of critical success factors for the successful implementation of Lean Six Sigma and Six Sigma in manufacturing small and medium sized enterprises. Issue Volume 30:Issues 3(2018) (3rd July 2018) - Stankalla, Roland; Koval, Oksana; Chromjakova, Felicita
ABSTRACT: Organizations embarking on implementation of Lean Six Sigma and Six Sigma improvement initiatives need to overcome substantial barriers to ensure effectiveness of the implemented approaches. In many cases, implementation of improvement initiatives involves significant investment in establishment of supporting infrastructure and training for the improvement initiatives. While Lean Six Sigma and Six Sigma were initially applied within large corporations, the interest of small and medium-sized enterprises in improvement initiatives is increasing. Implementation of Lean Six Sigma and Six Sigma faces unique barriers in small and medium-sized enterprises associated with the size and availability of the resources. Thus, the aim of this article is to examine the critical success factors that condition successfulness of Lean Six Sigma and Six Sigma implementation in manufacturing small and medium-sized enterprises. Based on seven articles from six countries (the United Kingdom, India, Italy, Kenya, the Netherlands, and Malaysia), the importance of the different critical success factors are examined and compared. Further, the proposed study examines differences in the importance of the critical success factors between small and medium sized enterprises and large corporations. For the conduct of this analysis, six additional papers from Europe, India, and Brazil concerning critical success factors for the implementation of Six Sigma and Lean Sigma in larger manufacturing enterprises were taken into account. Moreover, five priority groups of critical success factors are developed for both organization sizes based on a percentile distribution. The analysis of the identified groups demonstrates similarities in the critical success factors for both types of organizations. In conclusion, it can be stated that "top management commitment" and "linking Six Sigma to business strategy" are the top priority critical success factors, for both small and medium-sized enterprises and large organizations. Additionally, for small and medium-sized enterprises, it is necessary to develop a good communication plan and link Six Sigma to customers.